Optimization of combined subcritical water and CO2 extraction for enhanced phenolics and antioxidant activity from coffee byproducts - Varunnarin karprakhon; Rinlada Sirisangsawang; Kanidta Kaewkroek; Thammasak Rojviroon; Natacha Phetyim; Somboon Sukpancharoen (Scientific Reports)
Abstract This study investigates the extraction of phenolic compounds and antioxidant activity from spent coffee ground (SCG) and coffee cherry pulp (CCP) using subcritical water extraction combined with high-pressure carbon dioxide (CO₂). The objective was to optimize extraction conditions to maximize total phenolic content (TPC) and DPPH radical scavenging activity. Using Design Expert V.13 and Central Composite Design (CCD), key parameters including extraction time (30–60 min), temperature (180–220 °C), and solid-to-water ratio (0.024–0.027 g/mL) were systematically analyzed. The optimal conditions for SCG were determined to be 198 °C, 0.027 g/mL solid-to-water ratio, and 60 min, yielding a TPC of 217.26 mg GAE/g DW and a DPPH value of 23.28 µMol TE/g DW. For CCP, the best extraction conditions were 189 °C, 0.024 g/mL solid-to-water ratio, and 54 min, resulting in a TPC of 230.13 mg GAE/g DW and a DPPH value of 32.63 µMol TE/g DW. The results indicate that CCP exhibited higher phenolic content and antioxidant activity than SCG, emphasizing its potential for valorization. Furthermore, Liquid Chromatography-Tandem Mass Spectrometry (LC-MS/MS) and Thin-Layer Chromatography (TLC) analyses confirmed the presence of bioactive compounds such as quinic acid, theobromine, and caffeine. These findings demonstrate the effectiveness of subcritical water and CO₂ extraction in enhancing the recovery of bioactive compounds from coffee byproducts. This optimized method provides a sustainable and solvent-free approach to extracting high-value phenolic compounds, with potential applications in functional food, nutraceutical, and pharmaceutical industries.